Trends in Rainfall and Economic Growth in Africa: A Neglected Cause of the African Growth Tragedy - Barrios, Salvador; Bertinelli, Luisito; Strobl, Eric (The Review of Economics and Statistics, 2010)
We examine the role of rainfall trends in poor growth performance of sub-Saharan African nations relative to other developing countries, using a new cross-country panel climatic data set in an empirical economic growth framework. Our results show that rainfall has been a significant determinant of poor economic growth for African nations but not for other countries. Depending on the benchmark measure of potential rainfall, we estimate that the direct impact under the scenario of no decline in rainfall would have resulted in a reduction of between around 15% and 40% of today's gap in African GDP per capita relative to the rest of the developing world.